Zgoda oskarżonego na orzekanie o warunkowym umorzeniu postępowania karnego (rozważania de lege lata i de lege ferenda) - Paluszkiewicz, Hanna (Wydział Prawa i Administracji UAM, 1996)
Conditional discontinuance of penal proceedings which is peculiar mean of penal responsibility may be applied only within regular penal case where there is a possibility of giving a sentence with some material contents. Penal code did not foresee any special form for to get such an act effective. The Author ponders what is the place and the role of the "consent" of the accused against the background of the other conditions of pronouncing conditional discharge. The accused can express his consent or his objection against a decision on a conditional discontinuance of criminal proceedings. We should admit that a change of the position of the accused in this question is allowed and, according to the projekt of new code of penal proceedings, it can be expressed in any form intelligible for the court.
Consent of the accused for conditional discontinuance of penal proceedings (remarks de lege lata and de lege ferenda)